Implementation of Accounting Standards for Cryptocurrency Companies in Indonesia - Janggur, Metodius France Marjun; Nugrahanti, Trinandari Prasetyo (Journal of Asian Business Strategy, 2022)
The development of number of cryptocurrency startups around the world, including in Indonesia, is increasing every year, demanding business people to provide financial services by accepting the presence of cryptocurrency technology directly in the real world. The purpose of this study is to explore the application of the Statement of Financial Accounting Standards (PSAK) adopting International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) on cryptocurrency companies at the Indonesian National Indodax Company (Bitcoin Indonesia). This research method is descriptive qualitative with data collection methods using interview and observation techniques. The results show that the Indodax Company (Bitcoin Indonesia) uses IAS 2 inventory because the company’s core business is in brokerage, which measures cryptocurrency inventory recorded at fair value after deducting costs to sell and is recognized in the income statement and reported in the Available for sale financial asset account. At the same time, the entity applies IAS 38 intangible assets in the measurement, valuation, and presentation of financial statements that refer to computer software and internet domains, not cryptocurrency assets in the form of coins and tokens. In addition, entities that measure and value cryptocurrency assets (cash and tokens) using financial instruments IFRS 9 Financial Instruments: Recognition and Measurement are calculated and recorded as financial assets at fair value through profit or loss (FVTPL).